Development of Augmented Reality Sex Education Media to Prevent Sexually Deviant Behavior for Male Students With Intellectual Disability - Tri Budi Sasongko; Wiwik Widajati; Asri Wijiastuti (Journal of General Education and Humanities, 2026)
Individuals with intellectual disabilities often face cognitive limitations in understanding abstract social boundaries, increasing their vulnerability to sexual deviance. This study aims to develop Augmented Reality (AR) media that provide concrete 3D visualizations, addressing the gap in safe, interactive sex education for this population. This research followed the ADDIE model, prioritizing Safe Content Design and Universal Design for Learning (UDL). The approach ensures that materials are cognitively accessible and socially appropriate for students with mild intellectual disabilities. Expert validation confirmed high feasibility with scores of 92% (media) and 87% (content). Field testing showed 90% practicality and a significant increase in effectiveness, with an N-gain score of 0.71. These results suggest that AR effectively bridges the cognitive gap by allowing repetitive simulations of social "Safe Zones" without triggering inappropriate arousal.